Circulating microbiome profiling in transjugular intrahepatic portosystemic shunt patients: 16S rRNA vs. shotgun sequencing - Zhang, Jingxiang; Xu, Xiaoshuang; Chen, Lei; Yang, Xincheng; Matsubara, Júlio Ken; Tian, Yuyao; Liu, Jiahua; Jin, Xiaoxu; Chang, He; Xu, Menghui; Zhu, Chunyang; Wang, Xin; et al. (Frontiers in Medicine, 2025)
Background and aimCurrent efforts to characterize the circulating microbiome are constrained by the lack of standardized protocols for isolating and sequencing microbial communities in blood. To address this challenge, our study compared 16S rRNA (V3-V4 region) and shotgun metagenomic sequencing for circulating microbiome detection.Materials and methodsAfter obtaining ethics committee approval and informed consent, samples were aseptically collected from 10 patients undergoing transjugular intrahepatic portosystemic shunt (TIPS) procedures. Shotgun metagenomic reads were taxonomically classified using the Kraken2-Bracken pipeline. 16S rRNA (V3-V4) data were analyzed through an ASV-based approach, with USEARCH for denoising and VSEARCH for taxonomic annotation. The results from both sequencing methods were then systematically compared.ResultsShotgun metagenomic sequencing generated 7,024,580,376 raw reads (mean depth: 234,152,679.2 reads/sample), while 16S rRNA sequencing produced 6,612,678 raw reads (mean depth: 220,422.6 reads/sample). 16S rRNA amplicon sequencing captured a broader range of microbial signals. Although the taxonomic profiles from both sequencing methods showed limited overlap, the core microbiota common to both were still identified. These conserved core microbial communities exhibited stable α- and β-diversity indices across separate vascular compartments.ConclusionIn our study, 16S rRNA amplicon sequencing captured more diverse microbial signals than shotgun metagenomics. A stable microbial community structure was observed across vascular compartments, suggesting a homogeneous microbial composition throughout the circulatory system.